How the United States benefits from agricultural and food security investments in developing countries - Board for International Food and Agricultural Development; International Food Policy Research Institute; Association of Public and Land-Grant Universities (International Food Policy Research Institute, 2019)
U.S. foreign agricultural assistance investments bring substantial economic, health, and security benefits to both developing countries and the United States. This report describes the food security investments of the U.S. Agency for International Development and how improving agriculture in developing countries brings positive returns to the United States and developing countries. The multiple benefits of foreign agricultural assistance include growth of agri-food systems of developing countries, and positive impacts on U.S. jobs and exports, technology spillovers that support U.S. agricultural production, health and nutrition of U.S. consumers, and global and U.S. security.